Everyday Cyborgs: On Integrated Persons and Integrated Goods. (22nd February 2018) - Quigley, Muireann; Ayihongbe, Semande
ABSTRACT: Using the metaphor and actuality of the 'everyday cyborg', this article makes the case that the law is ill-equipped to deal with challenges raised by the linking of the organic, biological person with synthetic, inorganic parts and devices. For instance, should internal medical devices that keep the person alive be viewed as part of the person or mere objects (or something else)? Is damage to neuro-prostheses (eg nervous system integrated limb prostheses) personal injury or damage to property? Who ought to control/own the software in implanted medical devices? And how should the law deal with risks around third-party device access (including that of unauthorised access and hacking)? We argue that satisfactorily answering such questions will likely require a re-analysis of the conceptual and philosophical underpinnings of the law, as well as the law itself. To demonstrate this, we examine the uncharted terrain which everyday cyborgs pose for the law, looking in particular at five areas: (i) medical device regulation, safety, and product liability; (ii) damage to devices and liability; (iii) data and privacy; (iv) security and biohacking; and (v) intellectual property rights. The article highlights how advancing biotechnology continues to reveal, and prompts us to confront, lacunae within the law. Our analysis calls particular attention to law's boundary-work (how the law utilises and incorporates supposed ontological and moral boundaries) and the challenges which everyday cyborgs pose to this.